Ach wie gut, dass niemand weiß ...? Anmerkungen zur Methodenwahl bei Institutsrankings - Peter Huber; Angelina Keil (Austrian Institute of Economic Research (WIFO), 2007)
– Two recent studies published in "Perspektiven der Wirtschaftspolitik" are used to discuss methods to develop bibliometric analyses and rankings of economic research institutions. According to them, standardisation methods using the number of staff or university graduates may have a crucial impact on results, especially when the weighting methods used are not sufficiently selective. Different methods to prepare the database also have considerable influence on the data quality and results. Rankings based on a variety of methods for weighting the quality are frequently highly correlated with each other, but they supply quite different placements for institutes.
Keywords: 330; Rankings Publikationstätigkeit empirische Wirtschaftsforschungsinstitute; Wirtschaftsforschungsinstitut; Ranking-Verfahren; Bibliometrie; Theorie; Deutschland; Österreich